An American family : a memoir of hope and sacrifice - Khan, Khizr, 1950- (New York : Random House, 2017)
"'I am an American patriot not because I was born here but because I was not. I embraced American freedoms, raised my children to cherish and revere them, and lost a son who swore an oath to defend them, because I come from a place where they do not exist.' In fewer than three hundred words, Muslim American Gold Star father Khizr Khan electrified viewers around the world when he took the stage at the 2016 Democratic National Convention. And when he offered to lend Donald Trump his own much-read and dog-eared pocket Constitution, his gesture perfectly encapsulated the feelings of millions. But who was that man, standing beside his wife, extolling the promises and virtues of the U.S. Constitution? In this urgent and timeless immigrant story, we learn that Khizr Khan has been many things. He was the oldest of ten children born to farmers in Pakistan, and a curious and thoughtful boy who listened rapt as his grandfather recited Rumi beneath the moonlight. He was a university student who read the Declaration of Independence and was awestruck by what might be possible in life. He was a hopeful suitor, awkwardly but earnestly trying to win the heart of a woman far out of his league. He was a brilliant and diligent young family man who worked two jobs to save enough money to put himself through Harvard Law School. He was a loving father who, having instilled in his children the ideals that brought him and his wife to America--the sense of shared dignity and mutual responsibility--tragically lost his son, an Army captain killed while protecting his base camp in Iraq. He was and is a patriot, and a fierce advocate for the rights, dignities, and values enshrined in the American system. An American Family shows us who Khizr Khan and millions of other American immigrants are, and why--especially in these tumultuous times--we must not be afraid to step forward for what we believe in when it matters most."--Dust jacket flap.
Khan electrified viewers around the world when he took the stage at the 2016 Democratic National Convention. When he offered to lend Donald Trump his own much-read and dog-eared pocket Constitution, his gesture perfectly encapsulated the feelings of millions. The oldest of ten children born to farmers in Pakistan, Khan was a university student who read the Declaration of Independence and was awestruck by what might be possible in life. He and his wife instilled in their children the ideals that brought to America, and then tragically lost a son, an Army captain killed while protecting his base camp in Iraq. Here Khan tells readers why we must not be afraid to step forward for what we believe in when it matters most.
Shoeless in a shaft of sunlight -- Twenty-one sparrows -- A stick becomes a ney -- Tomorrow will be better -- The wonders of the DMV -- Already American -- No man is complete until his education is complete -- Shining city -- Baba -- Always be a river -- God is found among the people.
Keywords: Khan, Khizr, -- 1950-; Pakistani Americans -- Biography; Muslims -- United States -- Biography; Iraq War, 2003-2011 -- Veterans; Immigrants -- United States -- Biography -- Juvenile literature; Muslims -- United States -- Biography -- Juvenile literature; Autobiographies; Biographies